Widely tunable spectrum translation and wavelength exchange by four-wave mixing in optical fibers - Marhic, M.E.; Park, Y.; Chiang, T.-K.; Kazovsky, L.G. (Optics letters, 1996)
Summary form only given. Wavelength conversion has been the subject of much research in recent years. Various methods have been studied with use of optical nonlinearities in either semiconductors or fibers. We introduce a novel technique based on four-wave mixing (FWM) in fibers, which has the potential for achieving unit conversion efficiency. It involves only spectrum translation, not inversion or phase conjugation. It is widely tunable and can, in principle, shift wavelengths by tens and even hundreds of nanometers. It can also perform a novel optical function, namely, complete exchange of optical power between two wavelengths.